2016
DOI: 10.1017/langcog.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Are all the triangles blue? – ERP evidence for the incremental processing of German quantifier restriction

Abstract: The present ERP study investigates the neural correlates of pictorial context effects on compositional-semantic processing. We examined whether the incremental processing of questions involving quantifier restriction is modulated by the reliability of pictorial information. Contexts either allowed for an unambiguous meaning evaluation at an early sentential position or were ambiguous with respect to whether a further restrictive cue could trigger later meaning revisions. Attention was either guided towards (Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 64 publications
2
34
0
Order By: Relevance
“…According to Nieuwland et al (), low autism values are indicative of a pronounced pragmatic sensitivity, and comprehenders with low AQ values are more likely to exhibit a pragmatic N400 effect (p. 329). Finally, in some studies, the N400 was accompanied by a late positive component, which has been suggested to reflect task‐related processing strategies associated with the verification process in general (Augurzky et al, ; Nieuwland, ).…”
Section: Background: Processing Of Scalar Implicatures In the Brain—ementioning
confidence: 94%
See 4 more Smart Citations
“…According to Nieuwland et al (), low autism values are indicative of a pronounced pragmatic sensitivity, and comprehenders with low AQ values are more likely to exhibit a pragmatic N400 effect (p. 329). Finally, in some studies, the N400 was accompanied by a late positive component, which has been suggested to reflect task‐related processing strategies associated with the verification process in general (Augurzky et al, ; Nieuwland, ).…”
Section: Background: Processing Of Scalar Implicatures In the Brain—ementioning
confidence: 94%
“…Event‐related potentials from three sentential positions (quantifier, color adjective, shape noun) were analyzed statistically by repeated‐measures anova s on mean amplitude values. Four regions of interest ( Rois ) were introduced (see Augurzky et al, ): left anterior ( Roi 1 : F3, F7, FC1, FC5), right anterior ( Roi 2 : F4, F8, FC2, FC6), left posterior ( Roi 3 : CP1, CP5, C3, P3), and right posterior ( Roi 4 : CP2, CP6, C4, P4). All analyses were calculated within an early N400 time window (300–400 ms) and a time window capturing late positive effects (450–800 ms) following Augurzky et al ().…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations